Analisis Kemampuan Pemecahan Masalah SD Pada Materi KPK dan FPB - Mamay Meilani; Anti Maspupah (Departement of Mathematics Education, 2019)
The study aims to analyze students' mathematical problem solving abilities in solving questions on the KPK and FPB material. This research is located at the Private Madrasah Ibtidaiyah Bongas 1. The research was conducted on October 7, 2019. The time was carried out when the Mathematics subject was in progress. This research was carried out specifically in class VI of Private Madrasah Ibtidaiyah Bongas 1 with a total of 25 students. This type of research is descriptive qualitative. Instrument is a tool used in collecting data to obtain data needed in a study. The instrument used in the study was a test in the form of 5 questions. Data analysis was carried out during and after data collection. The qualitative part is used to analyze students' learning difficulties when working on FPB material problems. Based on the results of the answers and interviews with students of Class VI Madrasah Ibtidaiyah Private Bongas 1, it can be concluded that (1). Students are not familiar with problem solving problems. (2). Students do not understand the steps in solving problem solving problems. (3) Students from the beginning did not know how to work on questions about FPB and KPK (4). Students find it difficult to work on FPB problems because students cannot perform multiplication and distribution operations which are prerequisite material from the KPK and FPB.